The use of next‐generation sequencing for the determination of rare blood group genotypes. Issue 3 (18th December 2017) - Jakobsen, M. A.; Dellgren, C.; Sheppard, C.; Yazer, M.; Sprogøe, U.
SUMMARY: Objectives: Next‐generation sequencing (NGS) for the determination of rare blood group genotypes was tested in 72 individuals from different ethnicities. Background: Traditional serological‐based antigen detection methods, as well as genotyping based on specific single nucleotide polymorphisms (SNPs) or single nucleotide variants (SNVs), are limited to detecting only a limited number of known antigens or alleles. NGS methods do not have this limitation. Methods: NGS using Ion torrent Personal Genome Machine (PGM) was performed with a customised Ampliseq panel targeting 15 different blood group systems on 72 blood donors of various ethnicities (Caucasian, Hispanic, Asian, Middle Eastern and Black). Results: Blood group genotypes for 70 of 72 samples could be obtained for 15 blood group systems in one step using the NGS assay and, for common SNPs, are consistent with previously determined genotypes using commercial SNP assays. However, particularly for the Kidd, Duffy and Lutheran blood group systems, several SNVs were detected by the NGS assay that revealed additional coding information compared to other methods. Furthermore, the NGS assay allowed for the detection of genotypes related to VEL, Knops, Gerbich, Globoside, P1PK and Landsteiner‐Wiener blood group systems. Conclusions: The NGS assay enables a comprehensive genotype analysis of many blood group systems and is capable of detecting common and rare alleles, including alleles not currently detected by commercial assays.